Calculation of Erosion Rate and Conservation Efforts in the Lut Tawar Sub-Watershed - Hiwana Alfadhila; Hairul Basri; Purwana Satriyo; Devianti; Syakur (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2026)
This study aims to analyze the level of erosion hazard (TBE) and formulate alternative soil and water conservation efforts that are appropriate to the conditions of the Lut Tawar Sub-watershed. The approach used is the integration of Geographic Information Systems (GIS) with the Universal Soil Loss Equation (USLE) method. Analysis of the magnitude of erosion (A) is carried out by calculating the rainfall erosivity factor (R), soil erodibility (K), slope length and gradient (LS), as well as plant management and conservation action factors (CP) in each land map unit (SPL). The results of the study show that the analysis of the erosion hazard level (TBE)—the potential for water erosion—indicates that the TBE value of 0.02 is included in the very light category. The TBE value in the range of 1.07–1.33 is classified as light, while the TBE value of 2.39 is included in the moderate category. Furthermore, the TBE value in the range of 3.95–6.51 indicates a severe level of erosion hazard, and the TBE value is very severe, namely 8.04 to 346.23. Overall, the TBE pattern at the site is classified as high, indicating that some SSTs are vulnerable to soil damage due to erosion. This is primarily influenced by a combination of very high actual erosion rates and relatively low Etol values in several soil types. Soil conservation efforts consist of mechanical conservation and vegetative conservation. Mechanical conservation includes the application of terracing and contour land management. Meanwhile, vegetative conservation is carried out through the planting of ground cover plants and the development of agroforestry systems on sloping land. This research can support sustainable management planning for the Lut Tawar Subwatershed and be used as a consideration in the formulation of soil and water conservation policies.